ANALISIS REALISASI PENERIMAAN DAN KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA BATU (Studi Kasus Dinas Pendapatan Kota Batu Periode Tahun 2009-2011) - Munthe, Susi Rugun (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Based on Law No.28 / 2009, Local Goverment (Batu) is allowed to make local tax collection. Collecting local tax in an area is adapted to the area’s potential and regional policies which is set by the Regional Regulation (Perda). The tax revenue target area in Batu that has been annualy determined is always enhanced by Batu Goverment and its achievement always exceeds the target, except in 2009 and 2010. The purpose of this study is to determine the local tax revenue, tax rate growth, and local tax revenues contribution toward PAD in Batu during the years 2009 to 2013. This study uses primary data and secondary data in the period 2009 to 2013, which were obtained from the Batu’s Goverment Office of Regional Revenue. The method used in this research is descriptive method with qualitative approach. Analysis done in 3 ways: data reduction, data presentation and conclusion. This study’s results indicates that the realization of Batu Local taxes in the period 2009- 2013 has increased each year and has met the targets even exceeded the target, except in 2009 and 2010. Local taxes became too the source of income that give most contribution to the PAD Batu ie by 62%, when compared with other types of revenue. The large amount of local taxes to PAD impact on local taxation policy which gives addition to te local tax objectfrom 6 types of local taxes into 9 types of local taxes. Keywords: Regional Income, Local Taxes, Revenues, Contributions areas